1996
DOI: 10.1002/pc.10645
|View full text |Cite
|
Sign up to set email alerts
|

Mesostructure development during molding of sheet molding compounds

Abstract: Experiments have been carried out with sheet molding compounds in which the amount of shear developed during molding was varied by changing the charge size. The effects of pressure and temperature were also investigated. The moldings were characterized by their mesostructures and the influence of the mesostructures on the Izod toughness and flexural strength was examined. It was found that high degrees of shear resulted in fiber orientation and the spreading of the fiber bundles. However, this did not improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Increased shear through mixing leads to bundle break up and a corresponding drop in impact resistance. Mei and Piggott [30] reported a similar effect when studying SMC material exposed to different degrees of flow (during the moulding process). It was observed that as the degree of flow during moulding increased, so the toughness was reduced.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Increased shear through mixing leads to bundle break up and a corresponding drop in impact resistance. Mei and Piggott [30] reported a similar effect when studying SMC material exposed to different degrees of flow (during the moulding process). It was observed that as the degree of flow during moulding increased, so the toughness was reduced.…”
Section: Resultsmentioning
confidence: 70%
“…Composite mesostructure describe mid-scale structures in composites, such as fibre alignment patterns, bundling effects, and fibre end synchronisation. The term is used by Piggott 1995 to describe mid-scale structures in composites in the size range 0.03-30mm [30]. This study attempts to investigate the extent of this influence, determining how changes in mesostructure affect physical properties.…”
Section: Introductionmentioning
confidence: 99%